Criminal Procedure Agreements in Polish Criminal Procedure: the Opinions of Judges and Prosecutors (Archives of Criminology, 2000)
Over the recent dozen years, there have been attempts in the criminal procedure doctrine at considerably re-formulating the airns of proceedings. It has been noticed, among other things, that the criminal process should not only tulfil substantive law. It has other aims as well that are just as important, including first and foremost liquidation of the specific “conflict” resulting from perpetration of an offence.This led to formulation of “post-classical” theories of the criminal process, stressing the consensual forms of conflict resolution that have been known since the birth of societies. Criticized was the assumption that the process seen as an instrument for fulfilling substantive law is in all cases the best form of conflict resolution and the best manner of legitimizing decisions of the agencies that apply the law (N. Luhmann, L. Morawski, T. Weigend, S. Waltoś).Consensual phenomena naturally arouse interest; they have become the topic of discussions. The real reason of such discussions is, among other things, a growing awareness of the poor efficiency of criminal justice: the disproportion of the means that can be used to fight crime to the actual needs in this respect.Already early in the nineties, the findings of a survey carried out within the Adam Mickiewicz University (A.J. Szwarc, J. Sobczak) demonstrated that agreements are alien to the Polish practice. The practice's opinion on that phenomenon varied in the survey: parallel to criticism, serious arguments were voiced for a broader use of agreements. This demonstrated the need for continued scientific discussion of the issue. The initial stage of that discussion was recapitulated at a conference held in June 1992 in Poznań. The conference provided the opportunity for the first direct confrontation of doctrine’s views.Several years later, a survey into formal and informal agreements was carried out within the Criminal Procedure Department of Jagellonian University (A. Światłowski). That survey also confirmed the existence in ptactice of a great variety of agreements, and the practice’s views proved just as diversified. The survey inquired about:1) the actual extent of agreements, or at least that declared by the circles involved;2) the appraisal of agreements by some of the legal professions;3) the possible postulates de lege ferenda voiced on the eve of introduction of new codification, especially with respect to the future formalization of some forms of adjustments made in the criminal process, and to suggested new regulations.The survey was divided into three parts: a pilot survey, interviews, and a mail questionnaire. Upon completion of the pilot survey, the stage of interviews started. Interviewed were judges of common courts and prosecutors public prosecutor’s offices, three from each unit selected for the sample. To secure a possibly even distribution of units, the country was conventionally divided into four areas. Within each area, one court of appeal, one provincial court, and two district courts were selected: one of them operating in a big city in an urbanized area, and the other one – in a smaller locality in a rural neighborhood. A similar procedure was applied to select l2 prosecutor’s offices (one provincial and two district ones in each area). Thus the planned sample to be included in the interview survey was to include 28 units, that is up to 84 persons. Foreseeable difficulties considered, such as refusals to be interviewed or a probable situation where as many as three judges deciding in criminal cases would not be present at the same time in one court, it was assumed that about 50 persons would be interviewed (the actual number was to prove bigger: 62).Besides, selected for the mail questionnaire were 4 courts of appeal as well as 48 each of provincial and district courts and prosecutor’s offices, that is the total of 100 units. Of the 300 mailed questionnaires, 141 (47%) were sent back. The questionnaire was anonymous.The findings have been discussed in the present paper. It has to be stressed that about a half of respondents considered informal and para-formal agreements possible. As regards the incidents of such phenomena, 63 respondents of the mail questionnaire never encountered the informal and para-formal agreements; instead, 75 (53.2%) had to do with them at least once. Characteristically, none of them chose the answer, “very often”.Among the interviewed persons, 29 (46.8%) had to do with agreements, while 33 (53.2%) never encountered that phenomenon.A great variety of answers were given to the question about the stage of proceedings at which agreements are made. Mentioned here were agreemets in preparatory proceedings (and even before the institution or that proceedings),  in proceedings before the 1st  instance cort, and also in the appellate proceedings.Almost all respondents who declared knowledge of the practice of agreements mentioned the sentence as the basic and standard subject of agreement. Of course, also adjustments in purely technical matters were mentioned here. What seems to have been the most typical phenomenon under the former code of criminal procedure was an agreement under which, most generally speaking, the defendant admitted his guilt and did not “obstruct” his conviction in return for a more lenient treatment.Mentioned most often (by 34, that is 44.7% of respondents) as the typical initiator of criminal procedure agreement was the counsel for the defense.As regards the categories of cases in which agreements were made, mentioned were socalled “family cases”, that is abuse and failure to pay maintenance, as well as petty thefts, sometimes combined with compelling a specific conduct or with destruction of property.The fact considered that the number of respondents declaring frequent contacts with agreements was not big, more attention has been devoted in the paper to the statements of those persons, and an attempt has been made at formulating conclusions as to the features of agreements made at the time of the survey.To end with, respondents were offered the opportunity to make suggestions as to formalization of agreements in the new codification that was about to be introduced at the time of the survey. The most frequent postulates no doubt concurred with the subsequently introduced new institutions, especially with the new institution provided for in Article 387 of the code of criminal procedure.